The Future of Hollywood Movie: Comparison Between Comic Adaptations and Hollywood Movie - Saptanto, Deswandito Dwi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The development of movies over time has evolved so rapidly. At the beginning, the process of making movies used very simple technology and mostly still used manual processes. Nowadays, the presence of a sophisticated film industry creates various digital effects to improve its visual appearance. The main focus of this study is to prove that the process of adaptation from comic to movies has undergone various significant developments. The process of making the movies currently applies more CGI (Computer-Generated Image) effects to facilitate the process of realization from static images to moving images. This adaptation process affects the results of the creation of the embodiment static images from comics into real-moving characters in the movies. This research uses qualitative descriptive method to examine the comparison that emerges from the process of Star Wars and Marvel Comics adaptation to movies. The result obtained is the similarity process of the creation on the adaptation of Star Wars movies into comics, while there are some significant differences in the process of adaptation of Marvel Comics into movies in Marvel Cinematic Universe. This study concludes that Star Wars and Marvel have different characteristics in the adaptation process from comics to movies or movies to comics. Star Wars still maintains its authenticity as a legendary canon masterpiece. George Lucas still tries to show the similarity of character manifestations as authentic and original forms. On the other hand, the process of adaptation from comics to movies carried out by Marvel often changes the original manifestation of the character to get more charming visual results and stronger characterization strength.